2021
DOI: 10.1158/0008-5472.can-20-3209
|View full text |Cite
|
Sign up to set email alerts
|

HDAC2 Facilitates Pancreatic Cancer Metastasis

Abstract: The mortality of patients with pancreatic ductal adenocarcinoma (PDAC) is strongly associated with metastasis, a multi-step process that is incompletely understood in this disease. Although genetic drivers of PDAC metastasis have not been defined, transcriptional and epigenetic rewiring can contribute to the metastatic process. The epigenetic eraser histone deacetylase 2 (HDAC2) has been connected to less differentiated PDAC, but the function of HDAC2 in PDAC has not been comprehensively evaluated. Using genet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…HDACs can regulate the progression of cancer cells 16 and HDAC2 is a Class I HDAC. Several studies have suggested that HDAC2 is crucial in cancer development 28–30 . However, the specific function of HDAC2 in NSCLC has not been comprehensively evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…HDACs can regulate the progression of cancer cells 16 and HDAC2 is a Class I HDAC. Several studies have suggested that HDAC2 is crucial in cancer development 28–30 . However, the specific function of HDAC2 in NSCLC has not been comprehensively evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic eraser histone deacetylase 2 (HDAC2) has previously been shown to be connected to undifferentiated pancreatic cancer [65,66]. A more recent study explored the role of this enzyme with regards to PDAC metastasis [67]. In this paper, the authors demonstrated that HDAC2 controlled metastasis in a genetically engineered mouse model, where the metastatic burden in Hdac2 deficient mice was drastically reduced.…”
Section: Metastasismentioning
confidence: 95%
“…HDAC2 regulated the expression of receptor tyrosine kinases, including platelet growth factor receptor α (PDGFRα), PDGFRβ, and epidermal growth factor receptor (EGFR) [31] . Epidermal growth factor (EGF) increased the expression of creatine kinase α (CK2α), which in turn, increased the expression of HDAC2 in HCC [32] .…”
Section: The Mechanism Of Hdac2-promoted Tumorigenesismentioning
confidence: 99%
“…Thus, HDAC2 might mediate EGFR signaling to promote cancer cell proliferation. HDAC2 suppressed the anti-oncogenic transforming growth factor β signaling pathway and mediated pancreatic ductal adenocarcinoma metastasis [31] . The SIN3 transcriptional regulator family 3 A (SIN3A)-HDAC1/2 transcription repressor complex silenced bone morphogenetic protein 6 (BMP6) expression, which increased the metastatic potential and oncogenic potential of melanoma cells by suppressing BMP6-activated mothers against DPP homolog 5 signaling [33] .…”
Section: The Mechanism Of Hdac2-promoted Tumorigenesismentioning
confidence: 99%